2017
DOI: 10.3892/br.2017.1029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anthocyanin-rich bilberry extract on bone metabolism in ovariectomized rats

Abstract: Abstract. Menopause is associated with increased oxidative stress, which serves a role, in part, in the pathogenesis of postmenopausal bone loss. Fruits and vegetables are rich in antioxidative nutrients and phytochemicals. Berries are a natural source of anthocyanins, and their intake may improve bone health. The aim of the present study was to determine the effect of an anthocyanin-rich bilberry extract (VME) on bone metabolism in an ovariectomized (Ovx) rat. Female Sprague-Dawley rats (12 weeks old) were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Van der Heijden et al [ 36 ] did not find significant changes in the total body weight, weight of liver and adipose tissue in obese mice receiving high-energy diet with 36% extract of anthocyanins. Neither Shimizu et al [ 37 ] revealed a significant impact of anthocyanins-rich bilberry extract (500 mg/kg bw/day for eight weeks) on the total body weight and weight of uterus in ovariectomized (OVX) rats. According to Damiano et al [ 38 ], the body weight was significantly increased in ZDF rats compared with controls, whereas red orange and lemon extract rich in anthocyanins in ZDF rats significantly restored these values.…”
Section: Discussionmentioning
confidence: 99%
“…Van der Heijden et al [ 36 ] did not find significant changes in the total body weight, weight of liver and adipose tissue in obese mice receiving high-energy diet with 36% extract of anthocyanins. Neither Shimizu et al [ 37 ] revealed a significant impact of anthocyanins-rich bilberry extract (500 mg/kg bw/day for eight weeks) on the total body weight and weight of uterus in ovariectomized (OVX) rats. According to Damiano et al [ 38 ], the body weight was significantly increased in ZDF rats compared with controls, whereas red orange and lemon extract rich in anthocyanins in ZDF rats significantly restored these values.…”
Section: Discussionmentioning
confidence: 99%
“…LABE exhibited strong antioxidant potency, as shown by its high DPPH and ABTS radical scavenging activity and reducing power (Figure 2), which can contribute to the inhibition of ROS production. The inhibitory effects of various flavonoid compounds, including quercetin [54], rutin [55], and luteolin [56], on osteoclast differentiation have been described, as have the antiosteoporosis effects of anthocyanin and anthocyanin compounds from bilberry and black currant, which inhibited osteoclast formation from osteoclast precursor RAW 264.7 cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…As age increases, sex hormone production decreases, resulting in diminished oxidative defense systems [ 34 ]. This weakening of cells’ oxygen-scavenging capabilities increases oxidative stress produced from reactive oxygen species (ROS), which in turn stimulates osteoclast differentiation [ 35 ], induces osteoblast and osteocyte apoptosis [ 36 ], and inhibits osteoblastogenesis [ 10 ], all resulting in suppressed bone formation. Bone formation rate also decreases due to the oxidation of lipids generating ligands that activate peroxisome proliferator-activated receptor gamma, attenuating Wnt signaling [ 10 ].…”
Section: Discussionmentioning
confidence: 99%